2005
DOI: 10.1002/pon.941
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related relationship communication in couples coping with early stage breast cancer

Abstract: This longitudinal study examined the association between three types of communication strategies couples may use to handle stressors they experience during and after breast cancer treatment and psychological distress and relationship satisfaction of women with early stage breast cancer and their partners. Mutual constructive communication, mutual avoidance, and demand-withdraw communication strategies as well as psychological distress and marital satisfaction were rated by 147 patients and 127 partners during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
231
5
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(269 citation statements)
references
References 21 publications
21
231
5
12
Order By: Relevance
“…In a study of women with early-stage breast cancer and their spouses, we evaluated the role of the communication patterns described by Christensen and Shenk in couples' distress and marital satisfaction. 126 Our findings suggested that less pressurewithdraw communication, less mutual avoidance, and greater mutual constructive communication of cancer-related problems were associated with less distress and greater marital satisfaction on the part of both partners.…”
Section: Dyadic Level Theoriesmentioning
confidence: 61%
See 1 more Smart Citation
“…In a study of women with early-stage breast cancer and their spouses, we evaluated the role of the communication patterns described by Christensen and Shenk in couples' distress and marital satisfaction. 126 Our findings suggested that less pressurewithdraw communication, less mutual avoidance, and greater mutual constructive communication of cancer-related problems were associated with less distress and greater marital satisfaction on the part of both partners.…”
Section: Dyadic Level Theoriesmentioning
confidence: 61%
“…111 Finally, pressure-withdraw occurs when a partner pressures the other to discuss a cancerrelated problem and the other partner withdraws. 126 Relationship-compromising behaviors can be viewed as including components of social support, socialcognitive processing, and behavioral marital theories.…”
Section: The Relationship Intimacy Model Of Couple Psychosocial Adaptmentioning
confidence: 99%
“…We noted that single women with breast cancer scored higher on the interpersonal sensitivity symptom, which suggest that they may be more susceptible to problems relating to appropriately understanding others and responding accordingly. Husband is an important source of family support and his emotional involvement and understanding of the spouse's cancer experience is directly associated with psychological adjustment and outcomes (Wimberly et al, 2005;Manne et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This can test a couple's usual communication pattern and can lead to a decrease in communication, increased uncertainty, and increased avoidance of talking about illness-related distress, leading to worse outcomes (Manne et al, 2006;Arden-Close et al, 2010;Song et al, 2012, Badr & Krebs, 2013. Thus, while the need to communicate increases for couples, communication often decreases over time after the diagnosis (Song et al, 2012).…”
Section: Introductionmentioning
confidence: 99%